Overexpression of a laccase gene, DiLAC17, from Davidia involucrata causes severe seed abortion in Arabidopsis - Wei, Xiaoru (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.